L'ausilio dello Sport nel Modello Gestaltico Integrato - 1Salvatore Renda, 1Angela Ciulla, 1Letizia Cacciabaudo, 1Milena Mazzara, 1Valentina Maltese; 2Francesco Scarito (Marp Edizioni, 2021)
Sport in the Integrated Gestalt model The baggage inherited from our western culture is characterized by the artificial division between those which are the elements of a single reality: the mind and the body. This split is also expressed through our language; we do not have a single word that allows us to say "I-body" but we refer to it by saying my body, as if it were an object we possess, not a part of the self. We often think we have a body, understood as something different from us, in reality we are the body and it is our own life. Gestalt therapy, as holistic body and emotional mediation therapy, considers the mind and body as inseparable aspects, seeks the unity of the person and considers the organism as a whole. Talking about a holistic model in sports psychology makes us understand how the concepts of body and mind no longer help us to describe the functioning of the human being / athlete in a performance. The work has a twofold objective: the integration of sport into the integrated Gestalt model and the creation of a new intervention model in sports psychology with the help of the integrated Gestalt model.